Matrix-based algorithm for text-data hiding and information processing - Vesić, Nenad O.; Simjanović, Dušan J. (Vojnotehnički glasnik / Military Technical Courier, 2013)
An application of differential geometry in hiding text-data is presented in this paper. This application is a generalization of similar previously presented methods. Matrix valued functions of more than one variable are used in text hiding. This method is covered by the corresponding programs in the MATHEMATICA software package and compared with the previously presented method.